The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adem.202201548
|View full text |Cite
|
Sign up to set email alerts
|

Textile Electronic Circuits from Laser‐Patterned Conductive Fabric

Abstract: Textile electronics have shown very promising results in remote health monitoring or personal thermal management. Meanwhile, textile‐based generators are researched to harvest energy from human motion and supply the electronics required for signal acquisition and transmission. Hence, there is a need to fully integrate electronic circuits directly onto textile to achieve self‐powered smart garments. Herein, a thermoadhesive conductive fabric is considered to realize textile electronic circuits. A laser‐based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In a prior study, textile conductive tracks with a width of 0.7 mm, fabricated from the same conductive fabric, demonstrated an elongation at break superior to 20%, [ 34 ] a property deemed advantageous for the development of textronic circuits. It is important that the electrodeposition process does not significantly compromise the stretchability of textronic circuits of the conductive tracks when considering the wearability of textiles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a prior study, textile conductive tracks with a width of 0.7 mm, fabricated from the same conductive fabric, demonstrated an elongation at break superior to 20%, [ 34 ] a property deemed advantageous for the development of textronic circuits. It is important that the electrodeposition process does not significantly compromise the stretchability of textronic circuits of the conductive tracks when considering the wearability of textiles.…”
Section: Resultsmentioning
confidence: 99%
“…Elongation at Break of Conductive Tracks: The evaluation of elongation at break of conductive tracks was done on 0.7 mm wide tracks, which in a prior study, [34] demonstrated an elongation at electrical break exceeding 20%. These tracks were cut and laminated on a polyester dogbones with the method described in Section 2.2.…”
Section: Mechanical Resistance Of the Resulting Copper-plated Textilementioning
confidence: 99%
See 2 more Smart Citations
“…53,54 A thermo adhesive conductive fabric is considered to realize textile electronic circuits, which is developed by a laser-based method. 55 Cleaning a substrate for the physical vapor deposition technology is one of preliminary processes; the resistance of the layers has been increased in comparison to the structures produced on the unmodified substrate when the modification of a textile composite substrate with the laser technology influence on the surface resistance of silver structures. 56 The main categories of electronic devices/technology for wearable e-textiles developments were listed in Table 2, they are integrated into E-textiles.…”
Section: Transmission and Communication Of Smart E-textilementioning
confidence: 99%